Exploring the restorative effects of urban blue–green spaces on human psychology: a case study of Qingdao city, China - Xinyu Zhuang (Journal of Asian Architecture and Building Engineering, 2025)
The continuous reduced access to blue–green spaces caused by climate change as well as the COVID-19 pandemic – which led to many being far away from nature, and narrowing the range of crowd activities and interactions – has resulted in mental illness, induced healthy and social problems. Mental illness has become one of the most serious health problems faced by humans. How can we curb mental illness and achieve close contact between people and nature? Blue–green space plays an important role. This study analyzes the characteristics of restorative environments of blue–green spaces on people’s psychology by factor analysis, expert evaluation and photo measurement methods. From the perspective of people’s health recovery experience and psychological response to the environment, the subjective measurement of psychological environment factors and restorative effect of physical factors are explored. Furthermore, this study also reveals people’s preferences for different landscapes and explores positive and negative impact on mental health restoration. Study plots are classified into four types, people prefer the landscape space which is spacious with prominent visual focus, harmonious colors and suitable blue and green viewing rate. This study puts forward space optimization strategies to improve blue–green space for green, low-carbon and sustainable cities.